Melacak Keterhubungan Sanad Tahfidz Studi Tokoh KH. Amiruddin Ulama Pembawa Sanad Tahfidz Di Kabupaten Situbondo - Rofiq, Ahmad Zainur; Musolli, Musolli (Al-Ulum: Jurnal Pendidikan Islam, 2024)
This research aims to trace the connectedness of the sanad of KH Amiruddin, a cleric who carries the sanad in the city of Situbondo. This study uses a descriptive qualitative approach using a living Qur'an approach with Karl Mannheim's theory to reveal the life biography of KH Amiruddin and its relationship with sanad tahfidz. The tradition of memorizing (TahfÃ®dz) the Qur'an is one of the many phenomena of Muslims in animating or presenting the Qur'an in everyday life. And in the Tahfidz program there is also the Sanadul Qur'an program, which is a genealogy that continues back to the prophet Mohammed. The aim of this research is to determine the connection between Sanad Tahfidz KH Amiruddin, the first sanad-bearing ulama in Situbondo City. Data analysis uses descriptive analysis methods. The review stage in this method is to collect descriptive data that is appropriate to the research topic. After the data is collected, the data will be analyzed and clarified. The results of this research are to obtain information about the genealogy of KH Amiruddin's sanad and its history, how to obtain the sanad of the Qur'an (Tahfidz) in the city of Situbondo, and the impact of sanad in this era.